Integrative nursing - Kreitzer, Mary Jo; Koithan, Mary (Oxford : Oxford University Press, 2014)
Integrative medicine is defined as healing-oriented medicine that takes account of the whole person (body, mind, and spirit) as well as all aspects of lifestyle; it emphasizes the therapeutic relationship and makes use of appropriate therapies, both conventional and alternative. This resource is the first complete roadmap to integrative nursing, providing a step-by-step guide to assess and clinically treat conditions through a variety of combined methodologies including wellness, lifestyle enhancement, and nutrition.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on February 17, 2014).
Keywords: Integrative medicine; Nursing -- Practice